Examining the Triggers, Signals, and Implications of Corporate Implosion: Lessons and Intervention Strategies for Private Universities in Africa - (:unkn) unknown (My University, 2024)
Corporate implosion, characterized by sudden organizational collapses and significant financial repercussions, necessitates a comprehensive understanding of its triggers, signals, and potential intervention strategies. This paper employs a literature review and synthesis approach to delve into existing corporate implosion research specifically focusing on defining triggers, early signals, and viable rescue mechanisms. The study investigates triggers contributing to corporate implosions, focusing on financial mismanagement and leadership failures. It underscores the intricate interplay between internal and external elements in the context of organizational failures. Through thoroughly examining existing literature, the paper aims to contribute to a deeper understanding of the dynamics leading to corporate implosions. Furthermore, this research extends its scope to explore the closure of private universities, particularly within the African context. The analysis highlights industry-specific factors that contribute to the closure of private universities, encompassing aspects such as market demand, program relevance, financial stability, governmental regulations, economic conditions, demographic shifts, and technological advances. By broadening the investigation to include private universities in Africa, the study offers insights into the unique challenges faced by educational institutions in the region. Ultimately, the findings of this study are intended to inform decision-makers and stakeholders in private universities about the multifaceted nature of challenges that can lead to closures. Recognizing these triggers and signals is crucial for implementing timely and effective interventions to safeguard the stability and sustainability of private universities in Africa.
Keywords: African Research